Analysis of Thermal-Induced Microstructural Changes in Nanoscale Zr/Nb Metal Layers after Proton Irradiation; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 18 - Lomygin A. D. Anton Dmitrievich; Krotkevich D. G. Dmitry Georgievich; Laptev R. S. Roman Sergeevich; Stepanova E. N. Ekaterina Nikolaevna; Sidorin A. A. Aleksey Anatoljevich; Orlov O. S. Oleg Sergeevich (2024, 2024)
Title screen